Printed highly bio-tolerant Ti/Nb/Ta alloys : Combination of elasticity and strength (Transactions on Additive Manufacturing Meets Medicine, 2025)
Titanium alloys are state-of-the art implant materials featuring good biocompatibility and osseointegration. Unfortunately, they have a high Young’s modulus of 108 – 115 GPa, which contrasts with the better elasticity of the human bones, having a Young’s modulus of 12 – 25 GPa. This mismatch increases the risk of stress-shielding and can lead to of implant rejection. In addition, the use of only biocompatible and non-allergenic elements is beneficial for an increased biocompatibility. Suitable alternatives are Ti/Nb/Ta (TNT) alloys, consisting exclusively of biocompatible elements, providing the favorable combination of high elasticity, strength, reliable fatigue properties and good biocompatibility
Keywords: bio-tolerant Ti/Nb/Ta alloys; stress-schielding; elasticity; Ti-alloy; low Young's Modulus; bone in growth; 3D printed Implant